Considerations for Establishing Peptide Receptor Radionuclide Therapy: A Nationally Coordinated, Collaborative, and Equitable Service for New Zealand - Steyn, Rachelle; Henderson, Andrew; Wells, Karin; Mead, Trish; Rennie, Yasmin; Hull, Avril; Meredith, Liana; Sullivan, Michelle; Simmers, Saskia; Davidson, Jenny; Hauraki, Tame; Damianovich, Dragan; Boyle, Veronica; Lawrence, Ben (World Journal of Nuclear Medicine, 2025)
Inspired by international frameworks, New Zealand established a nationally coordinated peptide receptor radionuclide therapy service. This article reflects on the key steps involved in building the service, including the formation of a national neuroendocrine tumor (NET) multidisciplinary meeting, the role of patient advocacy, and the integration of local research. The successful creation of the service, despite significant challenges, demonstrates the value of collaboration between clinicians, government, universities, and patient groups in achieving equitable, high-quality care.
Keywords: New Zealand; NET; PRRT; implementation; multidisciplinary; health equity